Українська нація: формування чи відновлення ідентичності? - Букрєєва, Ірина; Bukrieieva, Iryna; Чичановський, Ігор; Chychanovskyi, Ihor; Коваленко, Олександра; Kovalenko, Oleksandra (Волинський національний університет імені Лесі Українки (43025, м. Луцьк, просп. Волі, 13) Київський національний університет імені Тараса Шевченка (03680, м. Київ, просп. Акад. Глушкова, 4д), 2023)
The article attempts to scientifically reflect the prerequisites and semantic causes of russian aggression, which lie in an attempt to level Ukrainian identity as the determining basis for the existence and development of the nation. The idea of destroying everything Ukrainian has been dragging on for centuries, choosing different forms and methods. One of its tools was an artificially created inferiority complex, which was embodied through Russification. The russian-soviet empire tried for centuries to destroy the Ukrainian language, limiting the publication of books, modifying words and terms. Even during independence, there was a politicization of the language issue. The Ukrainian culture was also distorted, which the empire showed as primitive. The real history was replaced by pseudo-historical facts, which said that the Ukrainians do not have their own elite. To restore national identity, it is necessary to revive the historical memory that forms the historical consciousness and cultural code of the nation. It is they who testify that we are one nation, with its own territory, culture. In order to realize themselves and take their place among the peoples of the world, Ukrainians need objects of modern pride from the technological, scientific, information or economic spheres that would be progressive and characterize Ukraine as a postmodern and innovative state.

У статті здійснено спробу наукової рефлексії передумов та смислових причин російської агресії, які полягають у намаганні нівелювати українську ідентичність як визначальну засаду існування й розвитку нації. Зазначено, що ідея руйнування всього українського триває століттями, обираючи ті чи інші форми та методи гібридної війни. Одним із її інструментів був штучно створений комплекс меншовартості, який утілювався через політику русифікації. Російсько-совєтська імперія намагалася знищити українську мову, багату палітру культури, підмінити й переписати історію. Щоб відновити національну ідентичність, потрібно реанімувати історичну пам’ять, яка формує й історичну свідомість, і культурний код нації. Саме вони є свідченням того, що ми одна нація, зі своєю територією, культурою та героями. Щоб реалізуватися та посісти чільне місце серед народів світу, українцям потрібні предмети гордості сучасності з технологічної, наукової, інформаційної чи економічної сфер, які були б прогресивними й характеризували Україну як постмодернову та інноваційну державу.
Ukrainian Nation: Formation or Revival of Identity?
Keywords: російсько-українська війна; національна ідентичність; історична пам’ять; свідомість; Russo-Ukrainian war; national identity; historical memory; consciousness; культура; culture; 316.7